A Game for All Seasons: Lessons and Learnings from the JRC's Scenario Exploration System. (March 2020) - Bontoux, Laurent; Sweeney, John A.; Rosa, Aaron B.; Bauer, Alice; Bengtsson, Daniel; Bock, Anne-Katrin; Caspar, Ben; Charter, Martin; Christophilopoulos, Epaminondas; Kupper, Frank; Macharis, Cathy; Matti, Cristian; et al.
The European Commission Joint Research Centre's (JRC) Scenario Exploration System (SES) is a foresight gaming system developed to facilitate the application of futures thinking to policy-making. It was originally geared at engaging EU policy-makers with scenarios in a facilitated process with a low learning curve. Specifically, the SES was designed to help participants, in less than three hours, to engage in systemic thinking with a long-term perspective and to explore alternative futures on specific issues and themes. When applied in various contexts, the SES proved to have a broader range of applications, which led to communities of practice emerging around the tool. Successful responses to various requests to apply the tool beyond its original focus demonstrated the versatility of the SES. Specifically, we discovered its ability to accommodate a large array of scenarios to discuss a very diverse range of issues. The experience accumulated through several adaptations of the SES allows the analysis of the various strengths and weaknesses of the tool as a platform for futures thinking and sharing more broadly the know-how for the creation and application of new versions. Ultimately, this article seeks to contribute a series of design suggestions for futures practitioners seeking to develop a playful mode of interaction with scenarios, or those seeking to repurpose the original SES system for use in their own project.